Elucidating zerumbone’s low-efficacy agonism at the μ-opioid receptor via molecular dynamics simulation and Markov state modeling - Wan Mardhiyana Wan Ayub; Nurul Amirah Marjohan; Mohamed Haneif Khalid; Enoch Kumar Perimal; Muhamad Arif Mohamad Jamali (Springer Nature, 2025)
Indexed